Factors influencing corrosion of metal pipes in soils - Wasim, M.; Shoaib, S.; Mujawar, Mubarak; Inamuddin; Asiri, A. (Springer, 2018)
Deterioration of buried metal pipes due to corrosive soil environment is a major issue worlwide. Although failures of buried pipe due to corrosive soil is an old problem, yet such failures are still uncontrollable even with the application of advanced corrosion protection technologies. Therefore, understanding factors causing corrosion of buried pipes is necessary. This article reviews factors causing corrosion of buried pipes in soils. Factors include moisture content, soil resistivity, pH, dissolved oxygen, temperature and microbial activity. Moreover, we discuss the influence of manufacturing method and the comparison of corrosion behaviour of cast iron, ductile and mild steel pipes. We found that corrosion rate of pipes increases with moisture contents up to the critical moisture value. Although pH affects corrosion, there is no relationship between corrosion and pH and the corrosion rates of buried pipes are inversely proportional to soil resistivity. Soils containing more organic matter show high resistivity. Dissolved oxygen in soil develops differential cell which accelerates corrosion of metallic pipe. Different types of bacteria present in soil develop biofilms on metallic pipes, which deteriorates pipes with time.